Answer:
C. 11 3/4
Step-by-step explanation:
3 + 3 + 2 + 2 = 10
1/4 + 3/4 + 1/4 = 1 1/4
1/2 -> 2/4
2/4 + 1 1/4 = 1 3/4
10 + 1 3/4 = 11 3/4
Answer:
hmmmmmmmmm
Step-by-step explanation:
$12?
i think
Answer:
See below
Step-by-step explanation:
Your question is a bit unclear, so I'm going to assume you want the value of y or x:
(y+3)^2=-12(x-2)
-(y+3)^2/12=x-2
-(y+3)^2/12+2=x
(y+3)^2=-12(x-2)
y+3=sqrt(-12x+24)
y=sqrt(-12x+24)-3
2a+1 + 3a+2 +5a-9 you would start by combining like terms
2a+3a+5a= 10a
1+2-9= -6
10a-6=94
then subtract 94-6=88
then divide 88 by 10= 8.8
a=8.8
Answer:
<h2>3 + 4(n - 1)</h2>
Step-by-step explanation:
let r be the common differenc of the sequence
Term 12 - Term 7 = (12 - 7)r
then
47 - 27 = 5r
then
20 = 5r
then
r = 4
term 7 = term 1 + (7 - 1)r
then
27 = term 1 + 6r = term 1 + 24
then
Term1 = 27 - 24 = 3
<em><u>therefore </u></em>
the standard explicit formula of the sequence is :
term 1 + (n - 1)r = 3 + 4(n - 1)